Case report: Echocardiographic and computed tomographic features of congenital bronchoesophageal artery hypertrophy and fistula in a dog - Ji, Yewon; Kang, Jinsu; Heo, Suyoung; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2024)
Introduction: Studies on aberrant bronchoesophageal artery are limited. Herein, we report a case of a multi-origin systemic-to-pulmonary shunt with suspected bronchoesophageal artery hypertrophy and fistula in a dog. Case report: A 4-year-old castrated male beagle weighing 11 kg underwent routine medical screening. Physical examination revealed a right-sided continuous murmur of grade 1-2. Thoracic radiography revealed a mild cardiomegaly. Echocardiography revealed a continuous turbulent shunt flow distal to the right pulmonary artery (RPA) branch from the right parasternal short axis pulmonary artery view. Computed tomography demonstrated systemic-to-pulmonary shunts originating from the descending aorta at the level of T7-8, the right 5th and 6th dorsal intercostal arteries, and the right brachiocephalic trunk, which formed anomalous networks around the trachea and esophagus that anastomosed into a large tortuous vessel at the level of T6-7 and entered the RPA. Surgical ligation of multiple shunting vessels was performed. Postoperative echocardiography and computed tomography showed decreased left ventricular volume overload and markedly decreased size of the varices. Additionally, most of the shunting vessels were without residual shunt flow. Conclusion: The present study provides information regarding imaging features and the successful surgical management of multiple systemic-to-pulmonary shunts originating from the descending aorta, right brachiocephalic trunk, and intercostal arteries and terminating at the RPA. Multimodal imaging features after surgical ligation have also been described.메모 포함[예지1]: Reviewer 2 1 In line 56 the KvP and the mA of the radiographic technique is described. This should also include either the exposure time or, as an alternative, the mAs instead of the mA.